VD_FINDINFO HC / 2010 / 491 vom 17. Juni 2010 - VD Tribunal cantonal (2010)
INCAPACITÉ DE TRAVAIL, DURÉE, CONTRAT DE TRAVAIL, RÉSILIATION IMMÉDIATE | 324a al. 1 CO, 324a al. 3 CO, 336 CO, 336c CO, 337c al. 1 CO, 337c al. 3 CO, 341 CO, 343 CO, 451 CPC, 46 LJT